The Use of Role Play Model to Develop Vocabulary Mastery of Grade Ten Students at SMA Negeri 2 Palu - Priskila Angelika; Sriati Usman; Zarkiani Zarkiani; Hastini Hastini (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study, entitled The Use of Role Play Model to Develop Vocabulary Mastery of Grade Ten Students at SMA Negeri 2 Palu, aims to examine the effectiveness of the role play model in enhancing students’ vocabulary mastery. The research was motivated by the observation that many tenth-grade students at SMA Negeri 2 Palu struggle with limited vocabulary, which is often caused by low motivation, monotonous teaching methods, and a lack of confidence in using English. The study employed a pre-experimental design involving one group of 32 students. Data were collected using pre-test and post-test instruments administered before and after the implementation of role play activities based on real-life scenarios. The results showed a significant increase in vocabulary scores, with the mean rising from 12.06 (pre-test) to 18.75 (post-test). Statistical analysis using SPSS revealed that the data met normality and homogeneity assumptions, and the Independent Sample t-Test indicated a significance value of 0.000 (< 0.05), confirming the positive effect of the role play model. These findings support the conclusion that role play is an effective, interactive, and engaging strategy to develop students' vocabulary mastery.